ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF SPASIAL MATERI GEOMETRI DI SMA MUHAMMADIYAH 1 PURBALINGGA - Melinda, Septiana Dwi (AlphaMath : Journal of Mathematics Education, 2017)
This study aimed to analyze the students’ mathematical representation ability viewed fromspatial cognitive style on geometry. This study used qualitative method. Subjects in this studywere students X,MIPA 1 SMA Muhammadiyah 1 Purbalingga. The sampling technique of thisstudy was GEFT (Group Embedded Figure Test) by taking three students for a group of highspatial cognitive sytle, 3 students for a group of medium spatial cognitive sytle, and 3 studentsfor a group of low spatial cognitive sytle. Data analysis techniques used in this study werereduction of data (data reduction), description of data (data display) and conclusion(verification). Data collection techniques in this study were tests, interviews, anddocumentation. The results of this study indicate that high spatial cognitive style group is ableto master three indicators of representation, those are: recording and communicatingmathematical ideas in the from of symbol or picture on geometry using the words/ written textin solving geometry problems as well as creating mathematical model from the ideas byapplying mathematical expressions in solving geometry problems. While medium spatialcognitive style group is able to master two indicators, those are: recording andcommunicating mathematical ideas in the from of geometry symbol/image and written wordswritten texts in solving geometry problems. In addition, the low spatial cognitive style groupis able to master an indicator that is recording and communicating mathematical ideas in thefrom of geometry symbol or picture.Keywords: Mathematical Representation Ability, Spatial Cognitive Style